Seroprevalence of brucellosis and risk factors associated with its seropositivity in cattle, goats and humans in Iganga District, Uganda - Nguna, J.; Dione, Michel M.; Apamaku, M.; Majalija, S.; Mugizi, R.D.; Odoch, T.; Kato, C.D.; Tumwine, G.; Kabaasa, J.D.; Curtis, K.; Graham, M.; Ejobi, F.; et al. (Pan African Medical Journal, 2019)
Introduction: the burden of brucellosis among smallholder farmers is poorly-documented in Uganda. The disease burden is likely to be high, given the high levels of endemicity, lots of exposures and due to lack of control measures. In order to designate appropriate control measures, the magnitude and risk factors for brucellosis need to be known. We established the burden of and risk factors for Brucella seropositivity in cattle, goats, and humans in Iganga district, eastern Uganda.